2011
DOI: 10.5380/avs.v16i1.17926
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Macroscópicos E Histológicos Da Mucosa Gástrica De Ratos Wistar E Sua Utilização Em Modelo De Úlceras Gástricas

Abstract: RESUMO:A busca de novos fármacos e o uso de experimentação animal tem contribuído sobremaneira para o desenvolvimento da saúde, da ciência e tecnologia, promovendo ao longo dos anos a descoberta de medidas profiláticas e tratamentos de enfermidades que acometem os seres humanos. Animais de várias espécies têm sido utilizados desde os primórdios da civilização para o desenvolvimento científico, mas dentre todos os modelos experimentais aos quais podem ser induzidas úlceras gástricas, o rato Wistar, inquestionav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The muscular layer of the mucosa of the studied specimens was easily detected because of its location and cellular typicality, which refer to other mammals with simple stomach [4]. Moreover, it was observed in its broad totality that the findings in this study did not diverge from those observed on most domestic animals [1,12,18], particularly regarding the lining epithelium, organ stratification in layers or tunics and the presence of cellular and glandular constituents in each portion of the studied organ.…”
mentioning
confidence: 95%
“…The muscular layer of the mucosa of the studied specimens was easily detected because of its location and cellular typicality, which refer to other mammals with simple stomach [4]. Moreover, it was observed in its broad totality that the findings in this study did not diverge from those observed on most domestic animals [1,12,18], particularly regarding the lining epithelium, organ stratification in layers or tunics and the presence of cellular and glandular constituents in each portion of the studied organ.…”
mentioning
confidence: 95%